Children as Perpetrators of Crimes of Abuse (A Review of Restorative Justice Completion in Indonesia) - Moh Husen Alhasni (Universitas Negeri Gorontalo, 2023)
This research aims to explain the phenomenon of children as perpetrators of violent crimes and examine the restorative resolution approach in Indonesia. In recent years, there has been an increase in the number of cases of violence involving children as perpetrators in Indonesia. The existence of children as perpetrators of violent crimes raises serious concerns about the future of the younger generation and the security of society. The research method used in this writing is Juridical Sociological research and uses a qualitative research approach that is descriptive in nature and uses interactive analysis techniques. the research findings show that the restorative resolution approach has been recognized as a more effective alternative and focuses on victim recovery, offender development, and social reintegration. Restorative resolution involves a process of mediation and dialogue between the victim, offender and the community. The results show that this approach provides space for juvenile offenders to understand and take responsibility for their actions, while victims can express the psychological and emotional impact they have experienced.